Portion size tells who I am, food type tells who you are: Specific functions of amount and type of food in same- and opposite-sex dyadic eating contexts. (1st May 2017) - Cavazza, Nicoletta; Guidetti, Margherita; Butera, Fabrizio
Abstract: Previous research has shown that women eating small portions of food (vs. eating big portions) are perceived as more feminine, whereas men eating large portions are perceived as more masculine. The specific type of food items have also been shown to carry connotations for gender stereotyping. In addition, matching the co-eater's food quantity is also a means to ingratiate him or her. Thus, a potential motivational conflict between gender identity expression and ingratiation arises when people eat in opposite-sex dyads. Scholars have, thus far, focused their attention on one of these two dimensions at a time, and rarely in relation to the co-eaters' sex. The present study investigated, through a restaurant scenario, the way in which women and men, when asked to imagine having lunch in dyads, combine food choice and quantity regulation as a function of the co-eater's sex. Results showed that participants use the quantity dimension to communicate gender identity, and the food type dimension to ingratiate the co-eater's preferences by matching her/his presumed choice, following gender-based stereotypes about food. In opposite-sex dyads, dishes that incorporate the two dimensions were chosen above the expected frequency.